Short and stout as she was : relations inter-propositionnelles avec la structure « adjectif + as + sujet + be » - Bénédicte Guillaume (Discours)
This article deals with phrases introduced by an adjective (which may or may not be preceded by as or so), followed by as used as the subordinator of a finite clause constituted by a subject along with copular be (hereinafter referred to as “adj. + as”): short and stout as she was, that was the highest bit she could reach. The ambivalent link between “adj. + as” and the main clause deserves special attention, as it can be interpreted either in terms of a cause and effect relationship or of concession (paradoxical relationship); more importantly, the study of a corpus of about 240 examples (mostly sampled from the “Corpus of Contemporary American English” – COCA) confirms the intuition according to which the paradoxical interpretation of the relationship between the two clauses is overwhelmingly more frequent than the causal one (by a proportion of about ten to one in my corpus). The fronting of the adjective indicates that the adjective possesses a high degree of a certain quality, thus paving the way for a paradoxical interpretation, as this is often a subjective, non neutral, view of things. “Adj. + as” clauses may turn out to be ambiguous even in the presence of a main clause. It is doubtful, however, that “adj. + as” can merge both the logical and the paradoxical interpretations in its relation to the main clause, as they are too diametrically opposed from a semantic point of view to be able to combine coherently with each other within the same clause.